Sportorthopädie - Krause F; Dust K; Banzer W; Vogt L (Deutsche Zeitschrift für Sportmedizin)
Introduction: Several effects have been proclaimed for the use of elastic Kinesiotape (KT) for treatment or prevention of athletic injuries and performance enhancement. The aim of this study was to evaluate the prevalence as well as the subjectively-perceived effects of KT.Methods: An online questionnaire with open and closed questions was distributed among a cohort of exercise science students at a German university. Main outcome parameters were the subjective effects of KT concerning relief of complaints, (re-)injury rate and performance.Results: Of n=200 respondents (23.73.3 years; f=127), n=133 reported use of KT. A physiotherapist (PT) gave the recommendation for KT-use in 81%. Most commonly, KT was used in the therapy of musculoskeletal injuries (n=121), where 74% reported relief of complaints. When a PT or physician recommended KT, relief of complaints was significantly more likely (p<0.05). Overall, n=51 respondents used KT with the goal of preventing recurrent injuries. No re-injury occurred in 2/3 of the users.Discussion: The current study shows the high popularity and prevalence of KT among respondents, especially in therapy and prevention of musculoskeletal re-injury. The low rates of KT use in primary prevention and performance enhancement suggest minor importance in these settings. The majority of users were advised to use KT by a PT. Additionally, the recommendation by a PT or physician seems to positively influence subjectively-perceived therapy effects.KEY WORDS: Kinesiotape, Therapy, Injury Prevention, Questionnaire